Modernization, Innovation and Realization of the Chinese Dream: A Critical Review of Panmarketization Thinking Trend in China - Dongming, Xia; Guang, Tian (Journal of Applied Business and Economics, 2022)
To realize the great rejuvenation of the Chinese nation has been the most incredible dream for the Chinese people since the beginning of the 20th century. The Chinese dream is a massive historic economic and social project that requires all the Chinese people to work hard together. Since the reform and opening-up started 40 years ago, significant achievements have been made in China’s economic and social modernization. However, there are still problems that need to be addressed and resolved. It is undoubtedly necessary to explore the causes of the issues and strategies to remedy the defects. To realize the Chinese dream, Chinese people need to renovate their economic and social modernization concept. They need to create a new type of country with more muscular comprehensive national strength and finally realize the dream of the great rejuvenation of the Chinese nation.